Les outils SIG vus et vécus par les gestionnaires de crise à la Préfecture de Police de Paris - Fanny Di Tursi (EchoGéo)
Mapping tool are regularly present in the police institution of Paris’ departments. Crisis managers and operational agents use it every day in the context of their plural missions about operational intelligence, anticipation, command, and so on. These stakeholders often take action on same events to ensure security in a place and use to work on similar events. These agents manage events occurring ordinary but also, they manage crisis. Their tools are the same, or they are developed on a same framework, so we can interrogate the effective interoperability on tools between departments and about sharing data. Through these questions, we will present professions concerning GIS tools.